2017
DOI: 10.1080/21691401.2017.1379016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cellular characterization of various nano-assemblies of cell penetrating peptide-epirubicin-polyglutamate conjugates for the enhancement of antitumor activity

Abstract: A new class of cell penetrating peptides (CPPs) named peptide amphiphile was designed to improve the intracellular uptake and antitumor activity of epirubicin (EPR). Various amphiphilic CPPs were synthesized by solid phase peptide synthesis method and were chemically conjugated to EPR. Their corresponding nanoparticles (CPPs-E4 and CPPs-E8)were prepared via non-covalent binding of the peptides and polyanions. Cytotoxicity and anti-proliferative activity were evaluated by MTT assay. Cellular uptake was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…For example, to increase the penetration of NPs into the cochlea, NPs can be conjugated to cell penetrating peptides [76]. The antitumor activity of drug epirubicin (EPR) has been shown to be enhanced following conjugation of drug loaded NPs with cell penetrating peptides [77]. These findings hold a great potential to improve the penetration of drug loaded NPs into the cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…For example, to increase the penetration of NPs into the cochlea, NPs can be conjugated to cell penetrating peptides [76]. The antitumor activity of drug epirubicin (EPR) has been shown to be enhanced following conjugation of drug loaded NPs with cell penetrating peptides [77]. These findings hold a great potential to improve the penetration of drug loaded NPs into the cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…All peptides were synthesized manually by solid phase peptide synthesis (SPPS) method on CTC resin by Fmoc strategy using 60 ml innovative polypropylene syringes equipped with poly-tetrafluoroethylene (PTFE) filters, a Teflon stopcock and stopper [13][14][15][16]. The Fmoc protected amino acids with different side chain protecting groups used as the following derivatives: Fmoc-Arg (Pbf)-OH, Fmoc-Trp (Boc)-OH, Fmoc-Lys (Boc)-OH, Fmoc-Gly-OH, Fmoc-Gln (Trt)-OH and Fmoc-Glu (OtBu)-OH.…”
Section: Cpp Synthesismentioning
confidence: 99%
“…Many studies have reported that polyglutamate can effectively reduce the cytotoxicity of cationic cell-penetrating peptides through covalent or non-covalent interaction [ 26 , 27 ]. The length and amount of polyglutamate can be adjusted to prevent toxicity while maintaining cellular uptake efficiency [ 28 ]. Furthermore, negatively charged polyglutamate can be utilized for structure stabilization and surface modification.…”
Section: Discussionmentioning
confidence: 99%